Kompetensi Sumber Daya Manusia, Pelatihan Penyusunan Laporan Keuangan dan Penggunaan Teknologi Informasi dalam Mempengaruhi Kualitas Laporan Keuangan Pada Badan Usaha Milik Desa (BUMDes) di Kabupaten Gianyar - Noviantari, Ni Kadek Evita; Sumadi, Ni Komang (Hita Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of Human Resource Competence, Training on Preparation of Financial Statements and Use of Information Technology on the Quality of Financial Reports at BUMDes in Gianyar Regency. The population in this study were all BUMDes organizational management and village staff in charge of financial administration matters, totaling 342 people from 57 villages in Gianyar Regency. In this study, 171 participants were chosen using a purposive selection strategy and assessed using multiple linear regression analytic. According to the findings of this study, human resource competency has a beneficial influence on the quality of financial reports. Training in the creation of financial reports enhances their quality. The quality of financial reporting is improved by the use of information technology. Given the findings of the study, the Village Owned Enterprises (BUMDes) in Gianyar Regency will be able to offer regular training on how to create quality financial reports in the future. This is important to do as an effort to improve the competence of employees. Besides that, optimizing the use of information technology also important to support employees in compiling good financial reports.